Development of LC/MS-MS method for analysis of polyphenols in Malaysian traditional vegetables - Haron, Normah; Arcot, Jayashree; Bucknall, Martin (2015)

(untitled)
Development and validation of an LC-MS/MS method suitable for the simultaneous quantification of phenolic acids and flavonoids is described. Analytes were separated on a C6-phenyl column, analysed using negative ion APCI selected reaction monitoring. The method is capable of analysing 14 compounds (9 phenolic acids and 5 flavonoids) in 85 minutes and uses deuterium-labelled 4-hydroxy-3-methoxy-d3-cinnamic acid (ferulic acid-d3) and 13C15-quercetin as internal standards. The results demonstrated that the method developed was reliable, specific and robust. Thus the method was successfully applied to analyse phenolic compounds in 18 different types of traditional Malaysian vegetables (both raw and processed) with 3 different fractions of phenolic acids. Gallic, ferulic, vanillic and caffeic acids were the most dominant phenolic acids, while quercetin, apigenin, kaempferol and luteolin were the predominant flavonoids in the samples studied.